2021
DOI: 10.1002/mabi.202100216
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Senescence of Human Vascular Endothelial Cells by Molecular Mobility of Supramolecular Biointerfaces

Abstract: Yes-associated protein (YAP), a transcriptional coactivator of the Hippo signaling pathway, has been widely implicated in vascular aging and diseases. For preventing vascular endothelial cell senescence, the design and development of biomaterials to regulate YAP activity are required. This study prepares polyrotaxane-coated surfaces with molecular mobility and clarifies the role of the mobility on vascular endothelial cell senescence through Hippo-YAP signaling. The polyrotaxane surface with high mobility indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
2
6
1
Order By: Relevance
“…This suggests that cancer cells recognize the molecular mobility of polyrotaxane surfaces and alter the subcellular localization of YAPs, which is consistent with our previous reports on the relationship between the molecular mobility of polyrotaxane surfaces and subcellular YAP localization in epithelial cells, hepatocytes, endothelial cells, and mesenchymal stem cells. [12,19,20,36] When analyzing the cellular morphology of polyrotaxane surfaces with different mobilities, A549 and BxPC-3 cells on the SPE-PRX 86 surface with low mobility exhibited greater spreading than those on the SPE-PRX 5 surface with high mobility, which is also consistent with our previous reports. [18,20] Other previous reports using various substrate properties, such as stiffness, [37][38][39] micropatterning, [40] ligand density, [41] and dynamic ligand screening [42] reported that the relationship between cellular spreading and subcellular YAP localization.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This suggests that cancer cells recognize the molecular mobility of polyrotaxane surfaces and alter the subcellular localization of YAPs, which is consistent with our previous reports on the relationship between the molecular mobility of polyrotaxane surfaces and subcellular YAP localization in epithelial cells, hepatocytes, endothelial cells, and mesenchymal stem cells. [12,19,20,36] When analyzing the cellular morphology of polyrotaxane surfaces with different mobilities, A549 and BxPC-3 cells on the SPE-PRX 86 surface with low mobility exhibited greater spreading than those on the SPE-PRX 5 surface with high mobility, which is also consistent with our previous reports. [18,20] Other previous reports using various substrate properties, such as stiffness, [37][38][39] micropatterning, [40] ligand density, [41] and dynamic ligand screening [42] reported that the relationship between cellular spreading and subcellular YAP localization.…”
Section: Discussionsupporting
confidence: 91%
“…[12,19,20,36] When analyzing the cellular morphology of polyrotaxane surfaces with different mobilities, A549 and BxPC-3 cells on the SPE-PRX 86 surface with low mobility exhibited greater spreading than those on the SPE-PRX 5 surface with high mobility, which is also consistent with our previous reports. [18,20] Other previous reports using various substrate properties, such as stiffness, [37][38][39] micropatterning, [40] ligand density, [41] and dynamic ligand screening [42] reported that the relationship between cellular spreading and subcellular YAP localization. These reports revealed that cells exhibited large spreading area promote nuclear YAP translocation, while cells exhibited small spreading area inhibit nuclear YAP translocation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…11 Lessmobile surfaces induced osteogenic differentiation of mesenchymal stem cells, whereas highly mobile surfaces induced adipogenesis, 12 cardiomyogenesis, 13 and delayed cellular senescence. 14 By suppressing the actin filament formation with molecular mobility on the surface, progenitor cells could keep their undifferentiated state. 15 In polymers, the mobility of the main chains is directly connected with the glass-transition Temperature (T g ).…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mobility of polyrotaxanes has been utilized to impart high levels of toughness, [ 8 ] degradability, [ 9 ] and molecular recognition properties [ 10 ] to synthetic or natural materials. [ 11,12 ] Previously, we designed cell‐adhesive materials coated with polyrotaxane‐based triblock copolymers [ 13,14 ] and demonstrated that molecular motility on the surfaces affects cellular responses and functions including cellular adhesion, [ 15 ] morphology, [ 16 ] differentiation, [ 17 ] protein secretion, [ 18 ] senescence, [ 19 ] and cell–cell adhesion. [ 20 ] The extent of molecular mobility on the polyrotaxane surfaces was estimated using a quartz crystal microbalance with dissipation monitoring and contact angle hysteresis analysis.…”
Section: Introductionmentioning
confidence: 99%